Β-Conglycinin induces the formation of neutrophil extracellular traps dependent on NADPH oxidase-derived ROS, PAD4, ERK1/2 and p38 signaling pathways in mice. Issue 1 (8th December 2020) - Liu, Xiao; Fu, Yunhe; Wang, Jingjing; Wu, Di; Li, Shuangqiu; Wang, Chaoqun; Yang, Zhengtao; Zhou, Ershun
Abstract : Schematic representation of β-conglycinin induced NETosis. Abstract : β-Conglycinin is one of the key thermostable anti-nutritional factors in soybean, which has strong immunogenicity that usually leads to weaning in some young animals such as piglets and calves and allergic reaction in rats. Neutrophils are involved in the pathogenesis of an allergy. However, the contribution of functional neutrophils to allergy needs to be clarified. The formation of neutrophil extracellular traps is a novel effector mechanism of neutrophils and has been extensively investigated in recent years. To the best of our knowledge, there is no information available on β-conglycinin-induced NETs. In this study, β-conglycinin-induced NET formation in mice was examined via immunofluorescence analysis and fluorescence microplate reader. The mechanism of β-conglycinin-induced NETs was investigated using inhibitors and fluorescent microplate methods. The results showed that β-conglycinin induced the classical characteristics of NETs, which mainly consist of DNA as the backbone and decorated with histones, myeloperoxidase (MPO) and neutrophil elastase (NE). Moreover, β-conglycinin significantly induced the formation of NETs in a dose-dependent way. NET degrading enzyme DNase I markedly reduced β-conglycinin-induced NETs, which suggests that β-conglycinin indeed triggered the release of NETs. Further investigation showed that the quantitation of NETs was markedly decreased by the inhibitors of reactive oxygen species (ROS)-derived-NADPH oxidase, ERK1/2, p38, Rac and PAD4 signaling pathways, indicating the crucial role of these signaling pathways in β-conglycinin-induced NETs. Furthermore, our findings revealed that β-conglycinin induced the formation of NETs, which is dependent on NADPH oxidase-derived ROS, ERK1/2, p38, Rac and PAD4 signaling pathways. This study is the first to demonstrate the underlying mechanisms of β-conglycinin-induced NET formation, and it could be helpful to understand diarrhea caused by β-conglycinin overexposure in young animals and provides the corresponding theoretical basis for clinical applications.